Kajian Kritis Tentang Jiwa (An-Nafs) dalam Pemikiran Islam (Perspektif Pendidikan Islam) - Ramli, Ramli; Harun, Hamzah; Aderus, Andi (Indo-MathEdu Intellectuals Journal, 2024)
This article aims to find out the essence of An-Nafs based on Islamic thought and explain An-Nafs and Islamic Education according to the interpretation of Islamic philosophers or thinkers. This research is carried out through a qualitative approach with a literature study approach. The preparation of the article is carried out by examining various sources that are directly related to the focus of this research. The main sources of research data are reference books and research articles published in various scientific journals and indexed by google scholar. Data collection was carried out using the keyword "an-nafs in Islamic thought". Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of the analysis show that An-nafs means that human beings in totality, substance, and nature of God, have a human essence consisting of a part of the spirit that is integrated with the body (body). Based on Al-Kindi's view, an-nafs is jauhar basit (a single substance) with divine and spiritual characteristics, has a noble and perfect meaning. An-nafs is a spiritual distance, so its relationship with the body is axal. Although an-nafs is united with the body, with which it can carry out its activities, but an-nafs remains separate and distinct from the body, so that it is eternal after death. According to Al-Ghazali, human beings consist of al-nafs (soul), al-spirit, and al-jism (body).